Electrochemical study on inhibitory effect of Aspirin on mild steel in 1 M hydrochloric acid - Prasanna, B.M.; Praveen, B.M.; Hebbar, N.; Venkatesha, T.V.; Tandon, H.C.; Hamid, Sharifah Bee Abd (Taylor & Francis Open, 2017)
Aspirin was investigated as a good corrosion inhibitor for mild steel in 1 M hydrochloric acid at a temperature region from 303 to 333 K. The computed inhibition efficiency increases by increasing the inhibitor concentration and decreases by increasing the temperature. The investigation was done by weight loss, electrochemical measurements such as Tafel polarization and electrochemical impedance spectroscopy. Inhibition effect is attributed to the adsorption of inhibitor on the surface of the mild steel. The Tafel method reveals that the Aspirin acts as a mixed type inhibitor. Activation parameters suggest that the adsorption process is exothermic in nature. SEM photographs of mild steel in the absence and presence of inhibitor visualize the adsorption layer on the surface of the mild steel.